FEATURES OF FORMATION OF MISCANTHUS PLANTING MATERIAL IN CONDITIONS OF DRIP IRRIGATION - Doronin V.A.; Sinchenko V.; Driga V.V.; Kravchenko Yu. A.; Polishchuk V.V.; Mykolayko V.P.; Polishchuk T.V. (Scientific Journal of Pedagogy and Economics, 2020)
To establish the biological characteristics of growth and development of plants and the formation of planting material of miscanthus under conditions of drip irrigation. Methods. Field, laboratory, visual, measuring, weight, mathematical-statistical. Results. Represented the effectiveness of cultivation of planting material of miscanthus under conditions of drip irrigation without the application of Maxi Marin absorbent and when it is added to the period of planting of the rhizome. High survival of miscanthus plants in transplanting them from growing to open ground is established. In the conditions of drip irrigation it was 4.9% (without absorbent) and 3.3% (for making absorbent) more than without irrigation was. Drip irrigation significantly influenced the plant height and the formation of stems, while the introduction of absorbent was observed only a tendency of increase of these indicators. Introducing absorbent in rainfed conditions has resulted in a substantial increase in the content of free water in the leaves of miscanthus. Drip irrigation has contributed to intensive growth of not only land mass, and the mass of roots that provided a significant increase in the yield of planting material - the rhizome. The average for years of research weight uterine rhizome in drip irrigation was greater in control (without absorbent) by 62.8%, or 917,9 g than the absorbent application, respectively, the 61.8% or 912,7 g compared to irrigated conditions. Conclusions. The use of an absorbent as in rainfed conditions without irrigation, and in drip irrigation did not provide the increase of biometric parameters of the plants, weight of roots and, consequently, the output of planting material - the rhizome. The increase of these indicators was significantly affected only drip irrigation. In drip irrigation without any absorbent and when it is added from one of the ovaries rhizomes obtained mass was 15-20 g in 1.5 and weighing 25-30 g in 1.4 times more compared to the cultivation of ovaries without irrigation.